CRITICAL THINKING AND COLLABORATIVE LEARNING: STUDENTS’ PERCEPTIONS - Dedeh Rohayati; Lilies Youlia Friatin (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This study aims to outline students' perceptions about the use of collaborative learning to foster critical thinking skills; and how the use of collaborative learning helps improve students' critical thinking. This study uses a qualitative case study involving 23 third semester students in the English Language Education Program of the Faculty of Teacher Training and Education Science forming into six groups consisting of 3-4 students. Primary data is the result of group interviews, which are analyzed through several steps such as transcription, coding, categorization, condensation, and interpretation. The results of this study provide evidence for the description of students' high perceptions of the use of collaborative learning to foster critical thinking skills. In addition, students have a great awareness of collaborative learning that influences critical thinking skills. In addition, they also believe that critical thinking offers many benefits, including: 1) building teamwork, 2) implementing discussion, 3) respecting each other, 4) saving time, 5) self-reflection, 6) reducing the workload, and 6) sharing knowledge. Apart from inadequate knowledge about critical thinking knowledge, students succeed in showing elements of their critical thinking by expressing opinions, making comments, drawing conclusions, solving problems, and producing effective arguments during the discussion process